CFD simulation of particle residence time distribution in industrial scale horizontal fluidized bed - Chen, K.; Bachmann, P.; Bück, Andreas; Jacob, M.; Tsotsas, E. (Powder Technology, 2019)
This work investigates the applicability of two conceptually different methods for simulation of particle residence time distributions (RTDs): the species method and the multi-solid method. Both are Eulerian methods; their key difference is found in the specification of the macroscopic particle dispersion coefficient and its relation to micro scale particle diffusivity. The intricate interrelation between particle diffusivity and dispersion coefficient was investigated. It is shown and discussed that, if a-priori knowledge on macroscopic dispersion is available, e.g. from correlations, the species method, which by definition requires data on microscale particle diffusivity, can be used directly with the macroscopic data in both, transient and steady-state simulation. If no such data is available, the multi-solid method has to be used which computes the dispersion coefficient directly, at greater computational expense. Additional advantages of the species model over well-known dispersion model are presented and discussed for the example of an industrial multi-chamber horizontal fluidized bed. (C) 2018 Published by Elsevier B.V.
CRIS-Team WoS Importer:2019-04-18